Fatigue service life of longitudinal reinforcement bars of reinforced concrete beams based on the real heavy traffic - Mascarenhas, Fernando Júnior Resende; Carvalho, Roberto Chust (Revista ALCONPAT, 2019)
This paper analyzes the fatigue service life of longitudinal reinforcement in reinforced concrete bridge beams by considering the actual number of heavy vehicles from 2 to 6 axes in a railway in the state of São Paulo, Brazil. Theoretical models with a structural system composed by bridges with two simply supported beams and spans of 10, 15 and 20 meters are used. Ftool is used to determine the internal stretches, and the cumulative damage method in the estimation of the fatigue life. At the end, it is verified that the fatigue service life of the longitudinal reinforcement varies according to the size of the span, and in the three analyzed bridges the fatigue service life is less than 30 years.